Determinants of awareness on Islamic microfinance among Cambodian Muslims - Sles, Alfin; Md Saad, Norma (International Society for Development and Sustainability, 2018)
This paper aims at examining the level of awareness among Cambodian Muslim towards Islamic Microfinance and to determine the factors that influence awareness. There are five independent variables investigated in this study namely: promotion, social culture, service quality, age, and level of education. A total of two hundred respondents consisting of Muslims living in different districts of Phnom Penh City responded to the survey questionnaire. The study used multivariate techniques to analyze the data collected. The findings showed that promotion and service quality were statistically significantly at five per cent (0.05) significant level. However, social culture, age and level of education were not significantly related with awareness. The findings also indicated that service quality had the most influence on awareness. Moreover, the result revealed that the level of awareness among Cambodian Muslims towards Islamic Microfinance was reasonable and the reasons for them preferring Islamic Microfinance were based on their religious principles and expectation of better services.